Diverticulectomy in the Management of Intradiverticular Bladder Tumors: A Twelve-Year Experience at a Single Institution - Ali Bourgi; Elias Ayoub; Sleiman Merhej (Advances in Urology)
Purpose. In this retrospective case review we analyze the outcomes of patients treated for intradiverticular bladder tumors (IDT). Materials and Methods. A retrospective case review was done between January 2002 and May 2014 in Hotel-Dieu de France hospital. The series included 17 patients diagnosed with IDT, all males with a mean age of 49.8 years. Results. One patient was treated with tumor resection and adjuvant BCG instillation with no recurrence on follow-up cystoscopies and urine cytologies. 64% of patients were treated by diverticulectomy. Mean follow-up time was 38.7 months. At the end of the follow-up, 81% were disease-free. One patient had a radical cystectomy 6 months after diverticulectomy for recurrent high grade tumor; another one had a nodal metastasis 10 months after diverticulectomy and was managed with chemotherapy. 29% of patients were treated with radical cystectomy. Mean follow-up time was 28.4 months. No recurrence was documented on annual CT scans. Conclusions. Our data support a conservative approach for tumors confined to the bladder diverticulum, even in high grade or in the presence of CIS provided complete removal is feasible and close follow-up is ensured.